Predicting Accuracy in Eyewitness Testimonies With Memory Retrieval Effort and Confidence - Gustafsson, Philip U.; Lindholm, Torun; Jönsson, Fredrik U. (Frontiers in Psychology, 2019)
Evaluating eyewitness testimonies has proven a difficult task. Recent research, however, suggests that incorrect memories are more effortful to retrieve than correct memories, and confidence in a memory is based on retrieval effort. We aimed to replicate and extend these findings, adding retrieval latency as a predictor of memory accuracy. Participants watched a film sequence with a staged crime and were interviewed about its content. We then analysed retrieval effort cues in witness responses. Results showed that incorrect memories included more “effort cues” than correct memories. While correct responses were produced faster than incorrect responses, delays in responses proved a better predictor of accuracy than response latency. Furthermore, participants were more confident in correct than incorrect responses, and the effort cues partially mediated this confidence-accuracy relation. In sum, the results support previous findings of a relationship between memory accuracy and objectively verifiable cues to retrieval effort.